Reference Librarians and LIS Students: Contrasting Views of Reference Source Training and Experience - Bossaller, Jenny; Adkins, Denice (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
An examination of students’ and practitioners’ attitudes towards, and uses of, various reference sources. Students found print sources to be educational, but use of print is waning. Many practitioners said learning specific sources was best done on the job, and felt new hires were better prepared to use online sources. La communication propose un examen des attitudes des étudiants et des praticiens à l’égard de différentes sources d’information et de leur utilisation. Les étudiants trouvent les sources imprimées éducatives, malgré une utilisation en déclin. Les praticiens trouvent que la familiarisation avec des sources précises se fait idéalement en milieu de travail et que les nouveaux embauchés sont mieux outillés pour utiliser des sources en ligne.